Effect of Membrane Hydrophobicity and Thickness on Energy-Efficient Dissolved Oxygen Removal From Algal Culture - Kishi, Masatoshi; Nagatsuka, Kenta; Toda, Tatsuki (Frontiers in Bioengineering and Biotechnology, 2020)
Removal of dissolved oxygen from algal photobioreactors is essential for high productivity in mass cultivation. Gas-permeating photobioreactor that uses hydrophobic membranes to permeate dissolved oxygen (pervaporation) from its body itself is an energy-efficient option for oxygen removal. This study comparably evaluated the characteristics of various commercial membranes and determined the criteria for the selection of suitable ones for the gas-permeating photobioreactors. It was found that oxygen permeability is limited not by that in the membrane but in the liquid boundary layer. Membrane thickness had a negative effect on membrane oxygen permeability, but the effect was as minor as less than 3% compared with the liquid boundary layer. Due to this characteristic, the lamination of nonwoven fabric with the microporous film did not significantly decrease the overall oxygen transfer coefficient. The permeability in the liquid boundary layer had a significantly positive relationship with the hydrophobicity. The highest overall oxygen transfer coefficients in the water-to-air and water-to-water oxygen removal tests were 2.1±0.03 ×10-5 and 1.39±0.09 ×10-5 m s-1, respectively. These values were considered effective in the dissolved oxygen removal from high-density algal culture to prevent oxygen inhibition. Furthermore, hydrophobicity was found to have a significant relationship also with water entry pressure, which needs to be high to avoid culture liquid leakage. Therefore, these results suggested that a microporous membrane with strong hydrophobicity laminated with nonwoven fabric would be suitable characteristics for gas-permeating photobioreactor.